2006
DOI: 10.1055/s-2004-830284
|View full text |Cite
|
Sign up to set email alerts
|

Zwang und Schizophrenie

Abstract: Co-occurrence of psychotic and obsessive-compulsive symptoms has been recognized for decades. This paper reviews published reports from five perspectives: schizophrenia with obsessive-compulsive symptoms, obsessive-compulsive disorder (OCD) with psychotic symptoms, schizophrenia-spectrum-personality disorder with obsessive-compulsive symptoms, obsessive-compulsive symptoms induced by atypical antipsychotics and similarities of functional neural circuits theory in OCD and schizophrenia. A MEDLINE search was con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…[2] In multiple studies, the prevalence of obsessive compulsive symptoms (OCS) and OCD in patients with schizophrenia have been reported from 7.8 to 64 percent and from 2 to 36 percent respectively. [3][4][5][6][7][8][9][10][11][12][13] Some of these differences can be explained with regard to different diagnostic criteria, assessment methods, duration of schizophrenia, difficulty in differentiating OCS from schizophrenia symptoms and from probable side effects of atypical antipsychotics. [6][10][13] In the past, the presence of OCS was considered to be an indicator of favorable prognosis of schizophrenia.…”
Section: Introductionmentioning
confidence: 99%
“…[2] In multiple studies, the prevalence of obsessive compulsive symptoms (OCS) and OCD in patients with schizophrenia have been reported from 7.8 to 64 percent and from 2 to 36 percent respectively. [3][4][5][6][7][8][9][10][11][12][13] Some of these differences can be explained with regard to different diagnostic criteria, assessment methods, duration of schizophrenia, difficulty in differentiating OCS from schizophrenia symptoms and from probable side effects of atypical antipsychotics. [6][10][13] In the past, the presence of OCS was considered to be an indicator of favorable prognosis of schizophrenia.…”
Section: Introductionmentioning
confidence: 99%
“…Fifteen review articles were selected as relevant. 5,[11][12][13][14][15][16][17][18][19][20][21][22][23][24] Ten articles were rejected because they did not meet the search criteria (articles on subclinical OCS). Additionally, 25 original research articles were identified after reference cross-checking and from the 15 selected relevant review articles.…”
Section: Articles Identifiedmentioning
confidence: 99%